Analisis Jejak Karbon Aktivitas Pendidikan Universitas Batanghari pada Masa Pandemi Covid-19 - Herawati, Peppy; Riyanti, Anggrika; Wiguna, Reiva; Ilham, M. (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to measure the amount of carbon footprint resulting from activities at Batanghari University during the Covid-19 pandemic. The analytical method used is carbon footprint calculation based on the GHG Protocol (The Greenhouse Gas Protocol) and guidelines from the International Panel on Climate Change. The research results show that the total carbon footprint of Batanghari University campus activities in the period June – November 2021 reached 399,843 tons.CO2-eq. This calculation was carried out in 3 (three) main areas, namely first, emissions from the use of official vehicles amounted to 0.0882 tons.CO2-eq and the use of LPG in the kitchen amounted to 0.107 tons.CO2-eq. Second, emissions from electricity use are 118,774 tons.CO2-eq/kWh, and paper use is 0.563 tons.CO2-eq. The three emissions from transportation activities amounted to 273,576 tons.CO2-eq, waste disposal amounted to 4.71 tons.CO2-eq, and LPG use in canteens amounted to 0.859 tons.CO2-eq.